Penegakan Hukum Pidana Terhadap Praktik Perjudian Berkedok Permainan Anak-Anak Di Pusat Perbelanjaan (Mall) di Kota Pekanbaru Oleh Polda Riau - Effendi, Erdianto (Jurnal Selat, 2018)
Abstract According to the Explanation of Law No. 7 of 1974 Gambling is one of the ailments of a society that is united with evil. From the data handled by the Riau Regional Police, the most revealed gambling case is gambling under the guise of a childrens play midfielder, which in practice is played by adults and contains elements of gifts. However, although some of them have been handled by Riau Regional Police Investigators, in the midst of the community we still encounter several games at the mall that can be qualified as gambling but towards those places as if they were untouched by law. This study concluded that law enforcement in the case of gambling under the guise of childrens games in shopping centers in Pekanbaru City was not optimal. In carrying out law enforcement, law enforcers in this case the investigator faced with the constraints of differences in the interpretation of gambling with the Public Prosecutor and the lack of concrete gambling arrangements in the Criminal Code.